Narratives and Computer: creating worlds and trying realities - Maria Cristina Palma Mungioli (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This paper presents the analysis of some narrative strategies used by students of Elementary School in the elaboration of texts. The texts were produced with the aid of a word and images processor (Microworlds). The analysis' perspective considers the recent researches on the narrative as way of understanding, representing and creating the reality. Some aspects of computer's use in the educational environment are also discussed. On this last aspect, some of the transformations concerning the relationship student-student, student-computer, student-teacher and student-knowledge were focused.